1986
DOI: 10.1093/infdis/154.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydia trachomatis Antigens by Enzyme Immunoassay and Immunofluorescence in Genital Specimens from Symptomatic and Asymptomatic Men and Women

Abstract: Chlamydia trachomatis antigens were detected in populations with the following infection prevalences: 26.5% (36 of 136) of men and 27.7% (48 of 173) of women attending a sexually transmitted disease clinic, 16.3% (53 of 324) of women attending a Planned Parenthood clinic, and 3.4% (4 of 117) of an obstetrics and gynecologic practice. Compared with cell culture of the combined female cervical specimens (15.8% prevalence), the respective sensitivities of Chlamydiazyme (Abbott Laboratories, North Chicago, Illinoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
0
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(59 citation statements)
references
References 30 publications
8
50
0
1
Order By: Relevance
“…In this study the prevalence rate was 15.2% among the target patients using EIA for antigen detec- tion. This result is comparable with the work done by Gilanfer et al [12] and Chernesky et a) [13]. The other workers like Mohaney et al [10], have shown higher prevalence rate.…”
Section: Discussionsupporting
confidence: 89%
“…In this study the prevalence rate was 15.2% among the target patients using EIA for antigen detec- tion. This result is comparable with the work done by Gilanfer et al [12] and Chernesky et a) [13]. The other workers like Mohaney et al [10], have shown higher prevalence rate.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, studies comparing the performances of these detection methods have frequently failed to consider biases that may occur due to the method of sample collection. The sensitivity of DFA testing reported in studies of women has ranged from 70 to 100% (6,27,92,96,134,140) (Tables 2 and 3); higher sensitivities generally have been reported in studies that used lower numbers of EBs as the cutoff number for reporting a positive test result. With a few exceptions (82,90,96), the specificity of DFA testing has been >95% for specimens from both males and females.…”
Section: Antigen Detection Methods For C Trachomatis Organismsmentioning
confidence: 97%
“…Although the high cost of chlamydial cell culture has been cited as a reason to use alternative test methods, cell culture when performed in quantity is competitive in cost with newer, nonculture methods (6,27).…”
Section: Specimen Transportmentioning
confidence: 99%
“…Deficiencies in culture and antigen detection assay sensitivities (6,13,17,21,32), as well as result reproducibility (18,24), have, in part, characterized past problems with laboratory testing for Chlamydia trachomatis. The sensitivities of culture assays for the fastidious pathogen Neisseria gonorrhoeae can be affected by the specimen collection device used (14), the viability of organisms in certain transport systems (27), and the various selective media used (33).…”
mentioning
confidence: 99%